Potential of STEAM-SDGs Integration in Physics Learning - Ajibudiarta, Riska; Khoiri, Nur; Patonah, Siti; Hayat, Muhammad Syaipul (Unnes Science Education Journal, 2025)
This study analyzes the potential of integrating STEAM (Science, Technology, Engineering, Arts, and Mathematics) with the Sustainable Development Goals (SDGs) in physics learning within Grobogan District, Indonesia, aligning with the National Long-Term Development Plan (RPJPN) 2025-2045’s focus on quality education. This descriptive qualitative research surveyed 23 physics teachers from the local MGMP (Subject Teacher Forum) using a questionnaire about STEAM-SDGs integration. Results revealed positive attitudes towards both STEAM (68% positive: 22% strongly agree, 46% agree) and SDGs (57% agree). However, understanding and application levels were low. 42% of teachers were undecided about STEAM, and 32% about SDGs. Regarding practical application, 37% were hesitant about STEAM implementation, and 29% about SDG integration. These findings highlight the need for comprehensive training to enhance teachers’ understanding and preparedness for integrating STEAM and SDGs into physics instruction. This is crucial for improving physics education quality and equipping students to address 21st century global challenges through innovative and sustainable learning.